Red honeybush (Cyclopia genistoides) tea mitigates oxidative imbalance and hyperlipidemia, while improving glucose homeostasis in type 2 diabetic rats - Xin Xiao; Ochuko L. Erukainure; Md. Shahidul Islam (Food Science and Human Wellness)
Red honeybush tea (RHT) is a tea product developed from Cyclopia spp. which is endemic to South Africa. Aside refreshment, RHT has over the years been used traditionally in the treatment of various diseases including type 2 diabetes. This study investigated the in vivo antioxidant and anti-diabetic activity of RHT concentrated hot water extract in type 2 diabetes (T2D) model of rats. T2D was induced starting with feeding 10 % fructose solution ad libitum for 2 weeks followed by a single intraperitoneal injection of streptozotocin (40 mg/kg body weight (BW)). Five weeks of treatment of RHT led to significant (P < 0.05) elevation in serum insulin, pancreatic β-cell function, HDL-c levels with concomitant decrease in AST, ALT, ALP, urea, CK-MB, fructosamine, total cholesterol, triglycerides, LDL-c, and insulin resistance in diabetic rats. RHT also significantly (P < 0.05) decreased MDA levels and enhanced level of GSH, activity of SOD, catalase, GR in most of organs (pancreas, liver, kidneys, and heart). Significantly (P < 0.05) improved morphological changes in the islets and β-cells were observed in rats treated with RHT. The data of this study suggest that RHT demonstrates an outstanding antioxidant and anti-diabetic effects in STZ-induced T2D model of rats.